The design and feasibility test of drive-thru market prototype based on Wemos as the learning media of internet of things (IoT) application - Rustam Asnawi; Ariadie Chandra Nugraha; Deny Budi Hertanto; Faranita Surwi; Indriya Galih Prayogi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
This research aims at (1) developing a learning media for the internet of things (IoT) applications in the form of Wemos-based drive-thru market module which is appropriate for Interface Engineering Courses at Electrical Engineering Education, Faculty of Engineering, Universitas Negeri Yogyakarta; and (2) determining the feasibility of the developed learning media. The subject of the research was the 2015 Mechatronics Engineering Education students. The object of the research was the drive-thru market prototype. The research instrument was the questionnaire to obtain data on media feasibility. The proper research results were in the form of (1) the hardware namely the drive-thru market prototype and it's Android application software, (2) the proper function of the prototype and Android applications with the design, (3) the feasibility from the media experts with the percentage of 78% and 83 % respectively that can be categorized as Appropriate, and from the user obtained the percentage of 86.15% with the category of Very Appropriate.